Ageing assets – workers get old too!. Issue 2 (3rd July 2017) - Snodgrass, Richard
Abstract: There is an increasing trend towards people working post 65 years. This is due to a number of factors: social, economic, political and psychological. Very little work has been done looking at the health and safety aspects of those people working beyond State Pension Age. Although there is research on post-65–year-olds, this mainly centres on people in care homes, looking at their mobility and social needs. Because this work has not been done specifically on older people in the work setting, it is difficult to use the results in any meaningful way for workplace issues, especially relating to workplace health and safety. This article looks at the potential impact of increasing numbers in the post-65-year-old workforce. It examines what is known about ageing in this cohort and its effects on workplace performance and health and safety. It then looks at some novel ways in which technology can extend working life. Finally, it identifies gaps in the knowledge base relating to the emerging phenomenon of the post-65-year-old worker.